L2 Learners’ Perceptions of Their Writing Strategies on an Intensive EAP Course - Mazgutova, Diana; Hanks, Judith (Journal of Academic Writing, 2021)
This study examines second language (L2) learners’ perceptions of their writing strategies on an intensive English for Academic Purposes (EAP) programme at a British university. The participants were 14 Chinese pre-undergraduate students who engaged in interviews and completed reflective journal entries. The results of the analyses indicate that after four weeks of studying on the EAP course, students believed that they started to apply a broader range of writing strategies, such as reading extensively, using exemplars of student writing to inform their own assignments, revising in a more focused manner and appreciating tutor feedback on their writing. Thus, the perceived increase in the use of various writing strategies is indicative of the potential effectiveness of a short EAP pre-sessional course.